MORPHOSTRUCTURAL ANALYSIS OF THE ITANHAÉM RIVER WATERSHED, SÃO PAULO STATE, BRAZIL - Cigagna, Cristiano [UNESP] (2022)
This research comprises the use of remote sensing products in the characterization of the natural susceptibility to erosion of the Itanhaém river watershed and its major tributaries, through morphostructural analysis. The method proved to be effective in mapping areas that are naturally sensitive to erosion, even when applied to different work scales. The most susceptible sectors are found upstream of the basin and mainly cover drainage areas of the rivers Mambú and Branco, where regions with the greatest vulnerability stand out. Another relevant aspect is that river follows its course embedded in an important shear zone, the Cubatão Fault. The discussion about the relationships between morphostructures and their altimetry is of great relevance for the analysis of the physical environment and to understanding the physiology of the landscape, as well for a more adequate indication of land use and occupation, as well the study of natural vulnerability.